PENGARUH MODEL PEMBELAJARAN STAD BERBANTUAN ARTICULATE STORYLINE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Kurnia Syabrinawati; Arnellis Arnellis; Edwin Musdi; Suherman Suherman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Mathematical problem solving skills are one of the essential skills that students must possess in mathematics education. However, these skills remain relatively low among seventh-grade students at SMP Negeri 25 Padang. One approach to addressing this issue is through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model, supported by Articulate Storyline. This study aims to describe the development of students’ mathematical problem-solving skills during instruction using the STAD model supported by Articulate Storyline and to compare the mathematical problem-solving skills of students learning with this model to those of students learning through conventional instruction. This study is a quasi-experimental study using a Posttest-Only Control Group Design. The results show that students’ mathematical problem-solving skills improved during the learning process, and the skills of students in the experimental class were better than those in the control class. Keywords: Mathematical problem solving skills; STAD; Articulate Storyline.   Abstrak: Kemampuan pemecahan masalah matematis merupakan salah satu kemampuan penting yang harus dimiliki peserta didik dalam pembelajaran matematika. Namun, kemampuan tersebut masih tergolong rendah pada peserta didik kelas VII SMP Negeri 25 Padang. Salah satu upaya untuk mengatasi permasalahan tersebut adalah melalui penerapan model pembelajaran kooperatif tipe Student Teams Achievement Divisions (STAD) berbantuan Articulate Storyline. Penelitian ini bertujuan untuk mendeskripsikan perkembangan kemampuan pemecahan masalah matematis peserta didik selama mengikuti pembelajaran menggunakan model STAD berbantuan Articulate Storyline serta membandingkan kemampuan pemecahan masalah matematis peserta didik yang belajar menggunakan model tersebut dengan peserta didik yang belajar menggunakan pembelajaran konvensional. Penelitian ini merupakan penelitian kuasi eksperimen dengan rancangan Posttest Only Control Group Design. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah matematis peserta didik mengalami perkembangan selama pembelajaran dan kemampuan peserta didik pada kelas eksperimen lebih baik dibandingkan kelas kontrol. Kata kunci: Kemampuan Pemecahan Masalah Matematis; STAD; Articulate Storyline.